The Diabetic Foot Medical and Surgical Management (Contemporary Diabetes, 2018)
In the fourth edition of this gold-standard title, a distinguished panel of experts provides a thorough update of the significant improvements in our understanding of diabetic foot physiology and its clinical management. Divided into three sections, the first part focuses on clinical features and diagnosis; the second on pathophysiology; and the third on the management of diabetic foot problems. In addition to updating all previous chapters, several new contributions have been added, reflecting advances in our understanding of the causes of diabetic foot ulcers and efforts to develop new and more effective therapies. The authors, many practicing at the famous Joslin-Beth Israel Deaconess Foot Center, again illuminate the successful new multidisciplinary approach now clearly required for successful treatment of the diabetic foot. Drawing on the experiences of diabetologists, podiatrists, vascular surgeons, infectious disease specialists, orthotists, plastic and orthopedic surgeons, The Diabetic Foot: Medical and Surgical Management, 4th Edition expertly describes standard techniques and current methods derived from the most recent data. This updated edition will be of significant value to all physicians and researchers with interest in a state-of-the-art understanding of the diabetic foot.